2021
DOI: 10.1093/tas/txab086
|View full text |Cite
|
Sign up to set email alerts
|

Degradability, in vitro fermentation parameters, and kinetic degradation of diets with increasing levels of forage and chitosan

Abstract: Chitosan is the second most important natural biopolymer in the world, extracted from crustaceans, shrimps, and crabs; and can modulate rumen fermentation. Our hypothesis is that the addition of chitosan alters the fermentation patterns of different diets for ruminants. This study aimed to evaluate the effects of different levels of chitosan and forage on in vitro dry degradation kinetics and fermentation in a gas production system. The chitosan levels (0, 1625, 3500 or 7500 mg/kg of DM) were arranged in a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Supplementation of 1-1.5% chitosan reduces actual DMD while increasing actual OMD and CPD. This result is in accordance with the studies by Wencelova et al (2014), Harahap et al (2020), andJacauna et al (2021) that the addition of chitosan to the diet decreases actual DMD and increases actual OMD and CPD. Because of the chitosan addition, the actual DMD in SE treatment decreased, which showed that SE treatments utilize slowly degrading materials as an energy and protein source in the rumen.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Supplementation of 1-1.5% chitosan reduces actual DMD while increasing actual OMD and CPD. This result is in accordance with the studies by Wencelova et al (2014), Harahap et al (2020), andJacauna et al (2021) that the addition of chitosan to the diet decreases actual DMD and increases actual OMD and CPD. Because of the chitosan addition, the actual DMD in SE treatment decreased, which showed that SE treatments utilize slowly degrading materials as an energy and protein source in the rumen.…”
Section: Discussionsupporting
confidence: 92%
“…Without impairing the feed digestion, chitosan shifts fermentation to a more energy-efficient pathway (Seankamsorn et al 2019). In contrast, some studies have found that chitosan significantly decreased IVDMD (Jacauna et al 2021;Wencelova et al 2014). Additionally, Goiri et al (2009) hypothesized that the composition of the basic diet, particularly the proportion of forage to concentrate, may have a significant impact on the efficacy of chitosan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation